Comparative Study on Outcome between Orthogonal and Parallel Plating in the Treatment of Distal Humeral Intra-Articular Fractures - Khaled Ibney Anwar,; Avijit Chowdhury,; Mahmudur Rahman,; Md Imrose Uddin,; Heba Hoque, (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Intra articular distal humerus fractures are complex injuries that can comsiderably limit elbow function if not treated properly. In the treatment of distal humerus intra articular fractures double plate osteosynthesis is the standard treat ment method. However, controversy still exists concerning the plate positions in terms of providing optimal stability of these kind of fractures. This study is aimed at finding any significant difference in outcome of these orthogonal and parallel plat ing methods of fracture fixation. Materials and methods: This quasi experimental study was undertaken to compare the differences between these two dual plating methods. It was conducted in Department of Orthopedics and Traumatology of Chittagong Medical College Hospital, Chattogram, for a period of fifteen months. 36 patients were enrolled conveniently according to inclusion and exclusion criteria. Patients were followed up for 6 months and overall outcomes were measured by MEPS. Depending on the overall functional outcome patients were grouped as having excellent to good outcome and fair to poor outcome. Results: At 6th month follow up, mean MEPS in the parallel plating group was 87.89±6.50 (Mean ± SD) and in the orthogonal group it was 83.72±7.45. There was no significant (p=0.785) difference between two groups in functional outcome but in parallel plating group MEPS was better. The mean union time was 6.17±0.383 weeks in parallel plating group and 6.22±0.548 weeks in orthogonal plating group. p value was 0.549. Regarding complications, elbow stiffness developed in 3(13.89%) in parallel and 4(19.44%) in orthogonal group, superficial infection developed 1 in parallel and 3 in orthogonal group. Conclusion: This study shows that, parallel plating group was superior to the orthogonal group, as of better functional outcome, less union time and less complications Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 36-41